[Installation of equipment at Brechin Castle Factory, Trinidad] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Installation of brass bearing onto the well roller (used to extract juice from the case) at the Brechin Castle Factory.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Sugar—Manufacture and refining—Equipment and supplies; Agricultural equipment -- Installation